Arquitetura, contrastes e escalas: o surgimento da capital moderna brasileira pelas lentes de Geraldo Vieira - Cunha, Larissa Ribeiro (2016)
This thesis proposes to analyze and discuss the unpublished collection of photographs of Brasilia - designed in seven mining expeditions by photographer Geraldo Vieira - from the first mass to the opening of the then new capital of Brazil. Also assess the importance of Geraldo Vieira through his photographic career, especially with regard to their stay in the city of Araguari-MG, in the Triângulo Mineiro, and its contribution to the historiography of it. Nevertheless, still point out the relevance of a unique collection of capital photographs Brasilia - that is most synonymous with the application of the principles of the Athens Charter in the world, which had the contributor and final editor architect Le Corbusier - to historiography and documentation of the Brazilian Modern Architecture. Geraldo Vieira was well as a photographer, a multifaceted artist whose skills are revealed both in photography and in other aspects of life. In this way, his legacy was able to influence not only in reception modes of modern source architecture, but also excited about the way in which people would like to be seen in his studio windows, in addition to promoting political issues discussed in social groups by contributing in journalistic photography and exhibitions publications. The search result appears from the explanation of the artist's path to an understanding of their involvement in photojournalism and to investigate its peculiarities as a photographic professional, so that you can reach in fact an investigation of photographic compositions of Brasilia, members his unpublished collection. An important guideline to this work also supports - in addition to the unprecedented nature of photographic documentation of Brasilia - is the approach of a study that could help and join efforts and reflections on the representation of Brasilia, to set the contrast of the photo analysis captured by a retired photographer axis Rio de Janeiro - São Paulo, which was active in the state of Minas Gerais.